Influence of antibiosis produced by actinomycetes on strains of Bradyrhizobium spp. on soybean nodulation - Pereira, João Carlos; Neves, Maria Cristina Prata; Drozdowicz, Adam (Pesquisa Agropecuaria Brasileira, 1999)
The aim of this work was to evaluate the antibiotic spectrum of actinomycetes from Cerrado soils and their influence on soybean nodulation. Strains BR 29, BR 33, BR 40, BR 85, BR 86, BR 96, 47/587, 3B-7 and 4A-5 of Bradyrhizobium spp. were characterized by their natural resistence to antibiotics produced by 204 actinomycete isolates. The strains BR 29 and BR 96 of B. elkanii were sensitive to 5.2% and 9.9% the products of actinomycete isolates, respectively, while BR 33 was sensitive up to 20.3%. The antagonistic effects caused by actinomycete exclusively to BR 29 and BR 33 were 1.6% and 5.7% respectively. This effect was not observed for strains BR 40 and BR 96. Single and multistrains inoculations in the presence or absence of actinomycetes affected soybean nodulation. On double strain inoculations, with BR 33 and BR 29 mixed with actinomycete 370 there was a decrease in nodule occupancy by BR 29 from 94.1% to 83.7% with concomitant increase in the occupying of BR 33 from 6.7% to 17.2%. The results indicate the importance of ecological studies on actinomycetes population in order to access their role in the establishment of efficient nodulation.
Keywords: cerrado; N2 symbiotic fixation; competition capacity; antagonism